2016
DOI: 10.1111/cdev.12565
|View full text |Cite
|
Sign up to set email alerts
|

Face Detection and the Development of Own‐Species Bias in Infant Macaques

Abstract: In visually complex environments, numerous items compete for attention. Infants may exhibit attentional efficiency—privileged detection, attention capture and holding—for face-like stimuli. However, it remains unknown when these biases develop and what role, if any, experience plays in this emerging skill. Here, nursery-reared infant macaques’ (Macaca mulatta; n = 10) attention to faces in 10-item arrays of non-faces was measured using eye tracking. With limited face experience, 3-week-old monkeys were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 107 publications
3
24
0
Order By: Relevance
“…Infant macaques present sensitivity for basic face structures (i.e., first-order relations, eyes above the nose, nose above the mouth). They prefer stimuli that respect face-like configuration192021, and prior work has revealed a similar sensitivity in human neonates2223. Later, between 3 and 12 months of age, human infants exhibit a perceptual tuning for faces in a way that makes processing and recognizing infrequently seen faces (e.g., monkey faces) more difficult24, a phenomenon likely driven by experience252627.…”
Section: Introductionmentioning
confidence: 85%
“…Infant macaques present sensitivity for basic face structures (i.e., first-order relations, eyes above the nose, nose above the mouth). They prefer stimuli that respect face-like configuration192021, and prior work has revealed a similar sensitivity in human neonates2223. Later, between 3 and 12 months of age, human infants exhibit a perceptual tuning for faces in a way that makes processing and recognizing infrequently seen faces (e.g., monkey faces) more difficult24, a phenomenon likely driven by experience252627.…”
Section: Introductionmentioning
confidence: 85%
“…Future studies should also examine category formation for face age in infants younger than 9 months, who are less experienced with faces from different age groups. Forthcoming lines of investigation could additionally focus on other aspects of visual perception such as face detection in complex visual arrays, contrasting categories of faces differing by age (for related work contrasting categories of faces by species, see Jakobsen, Umstead, & Simpson, 2016; Simpson, Jakobsen, Damon, Suomi, & Ferrari, in press). Such work would have theoretical significance given that infant faces have been shown to be attentionally prioritized by adults, in both humans (Brosch, Sander, & Scherer, 2007; Proverbio, De Gabriele, Manfredi, & Adorni, 2011) and monkeys (Koda, Sato, & Kato, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Paukner, Simpson, Ferrari, Mrozek, & Suomi, 2014). Such studies have revealed that, by 3 weeks of age, macaques can efficiently detect and look longer at faces compared with nonfaces (Simpson et al, 2017). Further, socially reared macaque infants exhibit early preferences for directgaze faces soon after birth (Muschinski et al, 2016) followed by the rapid development of gaze following in the first year of life (Rosati, Arre, Platt, & Santos, 2016), much like human infants.…”
mentioning
confidence: 99%